2012
DOI: 10.1021/ma301547n
|View full text |Cite
|
Sign up to set email alerts
|

No Reduction of CuBr2 during Cu(0)-Catalyzed Living Radical Polymerization of Methyl Acrylate in DMSO at 25 °C

Abstract: The Cu(0)/Me6-TREN-catalyzed polymerization of methyl acrylate (MA) initiated by methyl 2-bromopropionate (MBP) in DMSO at 25 °C was performed in a UV cuvette, and the absorbance of CuBr2 was monitored online in a UV–vis spectrophotometer as a function of the monomer conversion. A continuous increase of CuBr2 absorbance throughout the reaction demonstrated no reduction of CuBr2 concentration during the entire polymerization process. In addition, the 100% chain-end functionality of the polymer observed from 10%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 59 publications
8
82
1
Order By: Relevance
“…68 For example, although 100% retention of endgroup functionality was claimed in the literature, 74 the UV−Vis spectra showed that under the same conditions more than 1% of CuBr 2 /Me 6 TREN was formed with respect to the initiator. 126 This shows that at least 2% of the end groups were lost by termination, according to the principle of halogen conservation.…”
Section: Macromoleculesmentioning
confidence: 92%
See 1 more Smart Citation
“…68 For example, although 100% retention of endgroup functionality was claimed in the literature, 74 the UV−Vis spectra showed that under the same conditions more than 1% of CuBr 2 /Me 6 TREN was formed with respect to the initiator. 126 This shows that at least 2% of the end groups were lost by termination, according to the principle of halogen conservation.…”
Section: Macromoleculesmentioning
confidence: 92%
“…74,126,127 The key features of the SET-LRP mechanism are outlined in Scheme 5, presented in the same way as in Scheme 4, although some reactions are omitted in SET-LRP schematics, as shown in the middle part of Scheme 3. Therefore, SET-LRP does not include any significant kinetic contributions from alkyl halide activation by Cu I .…”
Section: Macromoleculesmentioning
confidence: 99%
“…As the SET-LRP of methyl acrylate (MA) is a well-studied and understood system, [40][41][42][43][44][45][46] the initiator-fixed silica nanoparticles were used to mediate the growth of poly(methyl acrylate) brushes from the particle surface. All polymerisations were carried out in DMSO at 30 °C using a Cu(0)/Me 6 TREN catalytic system in the presence of a free (sacrificial) initiator, ethyl 2-bromoisobutyrate (EBiB), unless specified otherwise.…”
Section: Resultsmentioning
confidence: 99%
“…The observation of disproportionation of copper(I) salts in water and of copper(I)/ligand complexes in DMSO led this group to propose that in these systems (and many others which had been considered to follow the ATRP mechanism) copper(0) was the primary activating species, and that concentrations of copper(I) were essentially zero as a result of rapid disproportionation. Additionally, the generation of copper(II) was thought to remove the need for build-up of copper(II) deactivating species via the persistent radical effect, thus providing low (or even zero (11)(12)(13)(14)) levels of termination from the beginning of the reaction.…”
Section: Scheme 1 Reactions Of Copper Metal In Atom Transfer Radicalmentioning
confidence: 99%
“…However, a detailed kinetic study of the polymerization of methyl acrylate in DMSO solution carried out by Percec and coworkers (11) showed that the rate of generation of copper decreased as the reaction proceeded. This was not a result of loss of dormant polymer chains through termination, which was less than 4% as estimated by the increase in copper concentration during the reaction (using the principle of halogen conservation (34)) and was too small to be measured by NMR (estimated at <0.5% by the authors of the study).…”
Section: Chain Length Dependence Of K T and K A0mentioning
confidence: 99%